STAT6(−/−) mice exhibit decreased cells with alternatively activated macrophage phenotypes and enhanced disease severity in murine neurocysticercosis - Mishra, Bibhuti B. (2010)
In this study, using a murine model for neurocysticercosis, macrophage phenotypes and their functions were examined. Mesocestoides corti infection in the central nervous system (CNS) induced expression of markers associated with alternatively activated macrophages (AAMs) and a scarcity of iNOS, a classically activated macrophage marker. The infection in STAT6(−/−) mice resulted in significantly reduced accumulation of AAMs as well as enhanced susceptibility to infection coinciding with increased parasite burden and greater neuropathology. These results demonstrate that macrophages in the helminth infected CNS are largely of AAM phenotypes, particularly as the infection progresses, and that STAT6 dependent responses, possibly involving AAMs, are essential for controlling neurocysticercosis.